The ’Never-Met’ Resistance of Urinary Tract Pathogens to Novel Antibiotics - da Cruz, Letícia Carolina; Maboni Siqueira, Franciele; Silva de Loreto, Erico; Ehrhardt, Alexandre; Zanette, Régis Adriel (Acta Scientiae Veterinariae, 2024)
Background: Antimicrobial resistance (AMR) is rapidly escalating among urinary tract pathogens, posing a pressing challenge for human and veterinary medicine. Urinary tract infections (UTIs), a common disease in humans and domestic animals like dogs and cats, are primarily caused by Gram-negative bacteria such as Escherichia coli, Klebsiella spp., Proteus spp., and Enterobacter spp. These pathogens are notorious for their ability to develop resistance against commonly used antimicrobials. Traditional antibiotics, particularly beta-lactams and fluoroquinolones, are losing their effectiveness due to the rising resistance levels. This alarming trend necessitates exploring novel antibacterial agents to manage and treat multidrug-resistant (MDR) pathogens. This study aims to compare the efficacy of the novel antibacterial agents cefiderocol, ceftolozane/tazobactam, eravacycline, lefamulin, and omadacycline with traditional antibiotics against MDR urinary tract pathogens from humans, dogs, and cats. Understanding the effectiveness of these new agents is crucial for developing better strategies to manage UTIs and combat AMR. Materials, Methods & Results: This study collected and analyzed urinary tract pathogens from humans, dogs, and cats between 2021 and 2023. The bacterial isolates, including E. coli, Klebsiella pneumoniae, Proteus spp., and Enterobacter spp., were identified using the Vitek system. The isolates showed resistance to at least 3 different classes of antibiotics, rendering them the MDR status. The efficacy of the novel antibiotics was tested using standard disc diffusion methods. Results showed that ceftolozane/tazobactam and omadacycline demonstrated nearly 100% effectiveness against the tested MDR strains. Cefiderocol and eravacycline exhibited intermediate efficacy, indicating their potential as front-line treatments for MDR infections. In contrast, the pleuromutilin lefamulin was the least effective, likely due to its action spectrum targeting Gram-positive pathogens rather than Gram-negative bacteria predominantly responsible for UTIs. A significant finding was the observed resistance in MDR pathogens to antibiotics not yet introduced in clinical practice, suggesting a preadaptive resistance mechanism. Discussion: The study underscores the critical need for developing and implementing novel antimicrobial agents to combat the growing threat of AMR. The high efficacy of ceftolozane/tazobactam and omadacycline against MDR urinary tract pathogens presents promising options for clinical applications, offering critical alternatives to traditional antibiotics that are becoming less effective. The intermediate success of cefiderocol and eravacycline further emphasizes their potential role as first-line treatments in managing MDR infections. However, the low efficacy of lefamulin highlights the importance of selecting appropriate antibiotics based on the specific pathogen involved. The discovery of preadaptive resistance in MDR pathogens to new antibiotics underscores the necessity for continuous surveillance, judicious antibiotic use, and integrated approaches in human and veterinary healthcare settings. These findings support the ’One Health’ approach, advocating for a collaborative effort to address health threats at the human-animal-environment interface. Effective stewardship programs and global monitoring are essential to preserve the efficacy of existing and future treatments, ensuring comprehensive management of UTIs. This study provides insights into the resistance patterns among urinary tract pathogens and reinforces the need for ongoing research and development in antimicrobial therapy. Keywords: urinary tract infections, multidrug resistance, novel antibacterials, humans, pets.